2009
DOI: 10.1073/pnas.0905684106
|View full text |Cite
|
Sign up to set email alerts
|

The GTPase Rab3b/3c-positive recycling vesicles are involved in cross-presentation in dendritic cells

Abstract: Antigen cross-presentation in dendritic cells is a complex intracellular membrane transport process, but the underlying molecular mechanisms remain to be thoroughly investigated. In this study, we examined the effect of siRNA-mediated knockdown of 57 Rab GTPases, the key regulators of membrane trafficking, on antigen cross-presentation. Twelve Rab GTPases were identified to be associated with antigen cross-presentation, and Rab3b/3c was indicated to be colocalized with MHC class I molecules at perinuclear tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…Peptide-loaded MHC II is transported to the cell surface for presentation to CD4+ T cells (Figure 1a). In the cross-presentation pathway, exogenously derived peptides are presented in the context of MHC I, as phagocytized bacterial antigenic peptides are loaded onto phagosomal MHC I, which is recycled from the cell surface (Figure 1b) [21], [25], [26]. The relative importance and functionality of this alternative pathway in mammals is still debated [21], [27].…”
Section: Introductionmentioning
confidence: 99%
“…Peptide-loaded MHC II is transported to the cell surface for presentation to CD4+ T cells (Figure 1a). In the cross-presentation pathway, exogenously derived peptides are presented in the context of MHC I, as phagocytized bacterial antigenic peptides are loaded onto phagosomal MHC I, which is recycled from the cell surface (Figure 1b) [21], [25], [26]. The relative importance and functionality of this alternative pathway in mammals is still debated [21], [27].…”
Section: Introductionmentioning
confidence: 99%
“…While NOX2 and Rac2 also regulate phagosomal acidification in CD8 + cDCs (Savina et al, 2009), only NOX2, but not Rac2, deficiency reduced CD8 + cDC cross-presentation of soluble antigen. Rab11a (Nair-Gupta et al, 2014), Rab3b (Zou et al, 2009) and Sec22b (Cebrian et al, 2011), which regulate vesicular trafficking, were shown to promote cross-presentation, but were studied using BM cultures treated with GM-CSF or in the DC2.4 cell line. In our studies, Mo-DCs generated with GM-CSF alone were relatively inefficient in cross-priming of cell-associated antigen compared with CD8 + cDCs and Mo-DCs generated with both GM-CSF and IL-4 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The isoform Rab3C was originally detected in one of the first phagosomal proteomes 11 and recently in phagosomes isolated from IFN-γ activated cells 14 . In a lentivirus-based siRNA screening, Rab3B/C was found to be required for antigen cross-presentation in dendritic cells 90 . Based on these observations, it is proposed that in dendritic cells, internalized bacteria in phagosomes and Rab3B/C-positive recycling endosomes may constitute an exocytic step of cross-presentation 90 …”
Section: Rab Gtpases Less Often Identified In Phagosomes and With Uncmentioning
confidence: 99%